A Comparative Study Between Open Prostatectomy Vs Transurethral Resection Of Prostate (Indian Journal of Applied-Basic Medical Sciences, 2022)
OBJECTIVE: To compare peri-operative and short-term complications of open trans-vesical prostatectomy (OP) as well as its functional outcomes with transurethral resection of the prostate (TURP) in management of benign prostatic hyperplasia with prostates sized 30 to 100g. METHODOLOGY: This is a prospective study conducted in the department of general surgery, GCS Medical College, Hospital and Research Centre from December 2019 to December 2020. 24 patients who were candidates for the prostate surgery with prostatesbetween 30 to 100 g, randomly underwent OP or TURP. Secondary endpoints included international prostate symptom score, residual urine volume, surgical complications, and patients’ quality of life. Patients were followed up for 6 months after the operation. RESULTOut of 24, 12 underwent OP and TURP respectively. Mean of peak flow rate improvement was 11.2 and 8 in OP and TURP groups, respectively. International prostate symptom score improvement did not reveal statistically significant differences between the treatment groups. Re-operation due to residual prostate lobe, urethral stricture, and urinary retention was performed in 3 patients in TURP group versus no patient in OP group. Dysuria was more frequent in patients that underwent TURP. Hospitalization duration was slightly longer in patients that underwent OP. CONCLUSION TURP is a valuable non-invasive surgical method with respect to absence of incision, effective symptom improvement and short hospitalization in BPH. Open prostatectomy easy to learning and more effective in large prostate size
Keywords: PROSTATECTOMY; TRANSURETHRAL